Anisotropy Engineering in 3D Magnetoplasmonic Nanoantennas - Gurunarayanan Prakash, Surya (My University, 2014)
The interaction between light and ferromagnetic nanostructures is investigated in this thesis. Studying the in uence of magnetic field on the surface plasmon properties and the associated enhancement of the magneto-optical (MO) response is becoming increasingly interesting due to advancements in nanofabrication and characterization [1]. Magnetoplasmonic devices find applications in sensing and telecommunication. In ferromagnetic materials the off-diagonal terms of the dielectric tensor can be activated (i.e., made non-zero) by the external magnetic field. These terms play a key role in the interaction of ferromagnets with light, producing interest- ing phenomena like Kerr and Faraday effects [2]. Ferromagnetic nanostructures of varying size, shape and thickness were fabricated in this work on glass substrates using hole mask colloidal lithography [3]. The optical and magnetic properties of these nanostructures can be controlled by these parameters. At the same time, their magneto-optical response can be effectively tuned by the localized plasmon excitations. Circular and elliptical nickel 2D nanostructures were investigated, followed by the increase in their height towards truly 3D magnetoplasmonic nanoantennas. The nanostructures were characterized by absorption spectroscopy and by the spec- troscopic magneto-optical Kerr effect (MOKE). Anisotropy in the particles played a key role in the tunability of the resulting Kerr polarization rotation. Different plasmon resonances (along x, y and z) of the nanostructures were engineered indi- vidually to achieve large enhancements in Kerr rotation. The out-of-plane plasmon resonance (along z) is shown to become more and more dominant in the definition of MO response as the structures grew in height,. This ultimately leads to a strong enhancement of MO response in these systems.
Keywords: Fysik; Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Physical Sciences; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship